Upaya Pemberdayaan Petani Kelapa (Cocos Nucifera) di Desa Pesaban, Kecamatan Rendang, Kabupaten Karangasem - ASTRINI, NI KOMANG TRI; SARJANA, I MADE; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
Coconut Farmers Empowerment Effort (Cocos Nucifera) in the Village of Pesaban, Sub-District of Rendang, Regency of Karangasem. Pesaban Village, Rendang Sub-District of Karangasem Regency has great coconut potential, but farmers can’t utilize the condition properly. The purpose of this research is to investigate: (1) coconut farming potential, (2) aspect and effort of empowering the coconut farmers. The research uses qualitative and quantitative analysis methods. The results showed that the potential of natural resources of coconut farming, human resources, and financial resources are good. Ownership of assets is good and belongs to the farmers themselves, relationships between individuals and groups are well established, coconut farmers have organizations to cooperate, and the partnership synergy of coconut farmers with the local and outside traders. Access to information is very less, the participation of the group has been well built, coconut farmers have a sense of responsibility in maintaining the good quality of the product, group forums have not fully be a problem-solving.